Structure and function of mucins, their role in tumor progression - Laskowska, Anna; Ugorski, Maciej (Contemporary Oncology/Współczesna Onkologia, 1999)
Mucin-type glycoproteins are produced by epithelial cells of gastrointestinal, respiratory and urogenital tracts as secreted or membrane-bound molecules. Their protein backbone is charakterized by the presence of repeating sequences rich in serine, threonine and proline residues. Mucins are highly glucosylated glycoproteins containing numerous O-linked oligosaccharides, often terminated in silic acid. The increasing number of evidence suggest that because of their extended, filamentous structures, negative charge, presence of specific carbohydrate structures they play a role in mucosal defence, cellular signalling and cell-cell interactions. Mucins undergo characteristic changes in their expression associated with neoplastic transformation. They are the carries of tumor-associated antigens, and probably one of the factors promoting metastasis.